A Leaf Curl Disease in Germplasm of Rapeseed‐Mustard in India: Molecular Evidence of a Weed‐Infecting Begomovirus–Betasatellite Complex Emerging in a New Crop. Issue 7 (29th March 2013) - Roy, Anirban; Spoorthi, Poreddy; Bag, Manas Kumar; Prasad, Telaprolu Venkata; Singh, Ranbir; Dutta, Manoranjan; Mandal, Bikash
Abstract Evaluation of 130 accessions of rapeseed‐mustard germplasm grown at the National Bureau of Plant Genetic Resources, New Delhi, India during the winter season (2011–2012) revealed the occurrence of a leaf curl disease in seven accessions. The occurrence of the disease was observed in another 62 of 525 accessions evaluated during 2012–2013. The association of a monopartite begomovirus and betasatellite was established with the symptomatic plants by whitefly transmission and PCR amplification. The complete nucleotide sequences of the begomovirus (JX270684, 2745 nucleotides), obtained by rolling circle amplification, showed the highest sequence identity (98.1%) with the weed‐infecting begomovirus, Croton yellow vein mosaic virus. Analysis of recombination indicated the probable occurrence of many overlapping inter‐ and intraspecific recombination events. The sequence of betasatellite (JX270685, 1355 nucleotides) showed the highest sequence identity (95.7%) with Croton yellow vein mosaic betasatellite. Begomoviruses were not previously known to naturally infect rapeseed‐mustard. This is the first report of the emergence of a weed‐infecting begomovirus–betasatellite complex in rapeseed‐mustard germplasm in India and raises the concern on utilization of such susceptible germplasm in crop improvement programmes.